2020
DOI: 10.3233/jad-200647
|View full text |Cite
|
Sign up to set email alerts
|

The Trajectory of Caregiver Burden and Risk Factors in Dementia Progression: A Systematic Review

Abstract: Background: Caring for patients with dementia at home is often a long-term process, in which the independence of the patient declines, and more responsibility and supervision time is required from the informal caregiver. Objective: In order to minimize and reduce caregiver burden, it is important to explore its trajectory and the accompanying risk factors as dementia progresses; the objective of this systematic review. Methods: PRISMA guidelines were followed in this systematic review. Three databases, PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 27 publications
1
77
0
1
Order By: Relevance
“…Several systematic reviews have identified that these stressors, which include demographic information of the people with dementia (e.g. education [ 10 ]), their health and functional status (including cognitive functionality [ 11 ], functional status [ 10 – 13 ], behavioural disturbance [ 10 , 11 ], neuropsychiatric symptoms [ 10 ]) and caregiver characteristics (e.g. relationship with person with dementia [ 13 ], cohabitation with care-recipients [ 10 , 13 ], caregiving load [ 10 ], coping style [ 11 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have identified that these stressors, which include demographic information of the people with dementia (e.g. education [ 10 ]), their health and functional status (including cognitive functionality [ 11 ], functional status [ 10 – 13 ], behavioural disturbance [ 10 , 11 ], neuropsychiatric symptoms [ 10 ]) and caregiver characteristics (e.g. relationship with person with dementia [ 13 ], cohabitation with care-recipients [ 10 , 13 ], caregiving load [ 10 ], coping style [ 11 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have concluded that BPSD predicted a higher burden of care. [8][9][10]21,32 This effect appeared to be primarily driven by disruptive behaviors (such as agitation, aggression, and disinhibition), followed by delusions and mood disturbance. 10 Disruptive behaviors had an adverse impact on the emotional connection between the caregiver and the care recipient and exacerbated difficulties in caring for the patients.…”
Section: Discussionmentioning
confidence: 98%
“…van den Kieboom et al 8 and Xiong et al 28 reported that being a female spouse is a risk factor for having a high burden when caring for people living with dementia. Care loads such as care duration and intensity (time spent on care per week) have been proven to be associated with the burden level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations